Heavy neutral leptons in gauged U(1) L µ −L τ at muon collider - He 何, Ru-Yi 如意; Huang 黄, Jia-Qi 佳琪; Xu 许, Jin-Yuan 金源; Yang 杨, Fa-Xin 法新; Han 韩, Zhi-Long 志龙; Shao 邵, Feng-Lan 凤兰 (Chinese physics C, 2024)
Heavy neutral leptons N are the most appealing candidates to generate tiny neutrino masses. We studied the signature of heavy neutral leptons in gauged at a muon collider. Charged under the symmetry, the heavy neutral leptons can be pair produced via the new gauge boson at the muon collider as and . We then performed a detailed analysis on the lepton number violation signature and at the 3 TeV muon collider, where the hadronic decays of W boson are treated as fat-jets J . These lepton number violation signatures have quite clean backgrounds at the muon collider. Our simulation shows that a wide range of viable parameter space is within the reach of the 3 TeV muon collider. For instance, with new gauge coupling and an integrated luminosity of 1000 fb , the signal could probe TeV. Meanwhile, if the gauge boson mass satisfies , the signature would be more promising than the signature.